An innovative thread-lift technique for facial rejuvenation and complication management: A case report. Issue 21 (May 2018) - Tang, Songjia; Sun, Zhongxin; Wu, Xiaoxin; Wang, Yu-Yan; Zhang, Jufang
Abstract: Rationale: Aging of face is an unavoidable process. Traditional procedures for facial rejuvenation have multiple disadvantages. In this case report, we used an innovative technique combining thread lift with small incision rhytidectomy for facial rejuvenation. Management for complication was also reported. Patient concerns: We presented a 52-year-old male with facial ptosis and wrinkles. Diagnoses: The patient was diagnosed as facial aging including skin laxity, mid-face and mandibular jowl ptosis, static crows-feet wrinkles, and deepening nasolabial fold. Interventions: We used an innovative technique combining thread lift with small incision rhytidectomy to treat facial aging. Outcomes: Improvements of the crow's feet, nasolabial fold, mid-face and lower face ptosis were observed. Complication of subcutaneous nodule was corrected with cosmetic effect of thread lift remained. Lessons: The innovative technique combining thread lift with small incision rhytidectomy is a good alternative for the treatment of facial aging.